Morphological floral characterization in accessions of Jatropha curcas L. - Pessoa, A. M. S.; Mann, R. S.; Santos, A. G.; Ribeiro, M. L. F. (Scientia Plena, 2012)
Knowledge of the structure of floral species is essential to achieving appropriate pollination techniques for the success ful breeding of controlled crosses. The goal of this work was to characterize the floral morphology of different accessions of physic nut (Jatropha curcas L.). Seventeen accessions were evaluated for proportions of staminate and pistillate flowers, average number of inflorescences per accession, and size of flowers. The J. curcas species is a monoecious plant, whose flowers are grouped in inflorescences. The average number of inflorescences per accession varied from 1.6 for JCUFS-014 to 23.7 for JCUFS-017. The staminate and pistillate flowers are pentamerous with actinomorphic symmetry and green coloration. The physic nut plant presented morphological variation for floral structure, related to the number of petals, sepals, floral glands, and stamens, and also presented hermaphrodite flowers.